Children’s Imitation and Word Creation in the Process of Language Acquisition - N. A. Trofimova; S. A. Shumilova (Дискурс, 2024)
Introduction. Since language acquisition is a gradual process, younger children have gaps in their mental grammar and mental lexicon. In order to be understood well while communicating with other people, they sometimes resort to creating new words, known as innovations, which remain unusual for the language norm. This article expounds the nature of children’s speech innovations and presents the analysis of their constructing.Methodology and sources. The research is based on data gathered within psycholinguistic experiment with participation of Russian-speaking children from three to six years of age. Such experimental methods of psycholinguistics research as picture description and story retelling were used.Results and discussion. It was found out that despite formal abnormality of speech innovations they are getting constructed according to rules existing in the language. Thus, innovations may include standard morphological units, which are combined with nonstandard ones with regard to their distributional features and restrictions. It means that morphemes commonly appearing, for example, on verbs will be used by children within this lexical category only. Moreover, a gradual increasing complexity of constructed forms is observed occurring with the age.Conclusion. Speech innovations cannot be conceived as errors, as they are constructed based on children’s knowledge about the language system and contain standard elements. Innovations analysed in this paper might be used for larger-scale studies on language acquisition and remain supplementary material for researches in this area.